BEBERAPA PENDEKATAN SOSIOLOGI DALAM PENELITIAN PERTELEVISIAN - Kurniawan, Donie Fadjar (Capture : Jurnal Seni Media Rekam, 2009)
â€œThis is a scientific writing related with Social Sciences in the frame of Television Research. In the view of research , the discipline of television department is a multi disciplines study. It is always colored wit h many others perspectives, such as psychology, social sciences, anthropology, economy even law. This writing explores how the social sciences can be applied in the television research. After all, mind, self and society have heavy influences as a frame of perspective research in media television or symbolic interaction, structural function and phenomenology also have huge influences as a frame of theoretical research. Television research is to examine group of television programs and its existenceâ€.Keyword : social sciences, television research, symbolic interaction, structural function, phenomenology